Health-Related Quality-of-Life Instruments for Pediatric Patients with Diverse Facial Deformities: A Systematic Literature Review. Issue 1 (July 2016) - Tapia, Viridiana J.; Epstein, Sherise; Tolmach, Oresta S.; Hassan, Abdul S.; Chung, Natalie N.; Gosman, Amanda A.
Abstract : Background: Treatment for patients with diverse craniofacial conditions is complex and long-term. Craniofacial conditions profoundly influence health-related quality of life, and patient- and parent-reported outcomes provide a critical and complementary perspective on the multidisciplinary treatment of patients. However, little is known regarding the health-related quality of life among children with diverse craniofacial conditions. The purpose of this study was to systematically review the literature regarding patient- and parent-reported outcomes measures for patients with diverse craniofacial conditions. Methods: Articles from the PubMed, PsychINFO, CINAHL, Embase/MEDLINE, Scopus, and Web of Science databases that used patient- and/or parent-reported outcome instruments in patients with diverse craniofacial conditions were reviewed. Diagnoses included were cleft lip and/or palate, craniosynostosis, microtia, craniofacial microsomia, facial vascular malformations, and congenital nevi across pediatric populations (0 to 22 years of age). Results: Six hundred ninety articles were identified, and 155 were selected for inclusion. One hundred twenty different health-related quality-of-life tools were used to analyze factors such as physical, psychological, or social function. Of these, the 10 most common psychometrically tested tools were identified in 59 studies. Five tools had both parent and patient versions. Two tools were developed and validated for patients with diverse craniofacial conditions, but neither was developed for nonadolescent children. Conclusions: Many parent- and patient-reported instruments are used to measure varying health-related quality of life factors in this population, but no tool exists that was developed and psychometrically tested in different facial deformities that measures comprehensive health-related quality of life issues across all pediatric ages. This study will guide the development of new tools to measure the parent and patient health-related quality-of-life perspective in patients with diverse craniofacial conditions. Abstract : Supplemental Digital Content is available in the text.